A Comparison of Select Aspects of Performance-Related Pay Between Local Companies and Branches of Multinational Companies Operating in Slovakia - Coculova, Jana; Baca, Lubos (European Scientific Journal, ESJ, 2016)
The subject of this paper is the issue of the transfer of performancerelated pay, as HRM practices, from the parent company to its subsidiaries. The aim of this paper is a comparison of performance-related pay between local companies and the branches of IC. For this purpose, research was carried out in the Slovak Republic in which the existence of statistically significant differences between the subsidiaries of multinational companies and local companies in selected aspects of performance-related pay was tested, such as the subject of performance-related pay, the time horizon of providing performance bonuses, and the composition of the performance fee (the proportion of fixed and variable components rewards). There were three hypotheses tested by using the Student’s t-test. The research results have shown the existence of differences in two of these studied aspects.